Answer:
![\phi=2.43\ rad=139.2^(\circ)](https://img.qammunity.org/2021/formulas/physics/college/ynglcc0zveri4ntcpuius29sq52lkzhgsv.png)
Step-by-step explanation:
The resultant wave of two identical traveling waves of amplitude
with a phase difference
between them is:
![Y(x,t)=y_Msin(kx-\omega t+\phi)+y_Msin(kx-\omega t)](https://img.qammunity.org/2021/formulas/physics/college/5i24obo9ccqmpata7bomxevpg6efrhsxg1.png)
Using the trigonometric formula
![sin(a)+sin(b)=2sin((a+b)/(2))cos((a-b)/(2))](https://img.qammunity.org/2021/formulas/physics/college/atrqrh5aech4n36unv6jdfrv53zewjb844.png)
we have:
![Y(x,t)=2y_Msin((2kx-2\omega t+\phi)/(2))cos((\phi)/(2))=2y_Mcos((\phi)/(2))sin(kx-\omega t+(\phi)/(2))](https://img.qammunity.org/2021/formulas/physics/college/qtepsiv6lbmszjcd80wdngmg0i30c04n05.png)
where we can see that the amplitude of the combined wave is
, which we want to be equal to
, so we do:
![2y_Mcos((\phi)/(2))=0.7y_M](https://img.qammunity.org/2021/formulas/physics/college/4tpcasjvx7qf9c4ncqyrr1ukbdiz47nsr7.png)
![cos((\phi)/(2))=0.35](https://img.qammunity.org/2021/formulas/physics/college/6edotk1h0rlo8hf90pqb22hdgn3vox68aa.png)
![\phi=2Arccos(0.35)=2.43\ rad](https://img.qammunity.org/2021/formulas/physics/college/yg1nfvem16w7e2so919ff0dlwdw6svuhfs.png)